Utilization of oil palm empty bunches waste as biochar-microbes for improving availability of soil nutrients - Ichriani, G I; Nion, Y A; Chotimah, H E N C; Jemi, R (Brawijaya University, 2016)
There are about 23% waste oil palm empty fruit bunches (OPEFB) of total waste generated from the production of crude palm oil in oil palm plantations. Pyrolysis technology can be used to convert waste into biochar and further can be utilized for the improvement of soil. Biochar-microbes of OPEFB are biochar from OPEFB biomass that enriched with soil microbes. Biochar-microbes is expected to be used for the improvement of the soil and plants. Therefore the purpose of this research was to study the ability of biochar-microbes OPEFB to increase availability of the nutrients in sandy soils. The process of making biochar done by using slow pyrolysis technology by heating 300oC and 400oC for 2 and 3 hours, and with sizes 40 and 80 mesh, as well as indigenous microbial Bulkhorderia nodosa G.52.Rif1 and Trichoderma sp.) added. The biochar production and research were conducted in the Department of Forestry Laboratory and in the Department of Agronomy Laboratory, Faculty of Agriculture, Palangka Raya University. In general, the study showed that biochar-microbes could maintain the soil pH value and tends to increase the soil pH, increasing the holding capacity of sandy soil to the elements of P and K as well as increasing the availability of nutrients N, P and K. Furthermore,Â this study showed that the biocharÂ process by 400oC heating for 3 hours and 40 mesh with microbes or without microbes were the best effect on the improvement of the quality of holding capacity and the nutrients supply in sandy soils.